The research on the negative emotional states and subjective well-being in cadets of higher military education institutions (Journal of Educational Sciences, 2021)
The specifics of both military service and educational requirements set high demands on stress tolerance and emotional well-being of cadets, which constitute a part of moral and combat training of military personnel for their professional activity. It is impossible to build an effective combat, academic, and psychological-pedagogical training of future officerswithout knowing their current psycho-emotional state and subjective well-being.The authors translated and adapted a set of methods for screening diagnostics of levels of anxiety, aggression, depression, and subjective well-being in Russian and Kazakh languages in the Kazakhstani sample. These methods are widely used worldwide but have not yet been adapted in Kazakhstan.An empirical study was carried out on a sample of 2 Kazakhstani higher military educational institutions in September and October 2021. A total of 597 cadets took part in the study. Correlational, cluster, and frequency analyses and other methods of nonparametric statistics were utilized, considering specifics of the data distribution and psychodiagnostic methods.The results demonstrate that, in general, most cadets display a low level of aggression (including hostility, physical aggression, anger), anxiety, depression, and a high level of psychological well-being. However, the frequency analysis shows that 18.4% of cadets report the presence of mild, moderate, and high anxiety; 13.07% report not quite comfortable or uncomfortable mental state (subjective ill-being); 36.5% experience a mild, moderate, and high levels of depression; 3 % of cadets display increased aggression level compared to average standard scores. Although the absolute values of anxiety, depression and aggression do not seem to be high, age, language, and the year of study influence their salience in future officers. The cluster analysis revealed the variables that contribute the most to the level of subjective well-being. The results will make it possible to develop more effective targeted psychological-pedagogical interventions aimed at enhancing the morale of cadets, creating an optimal psychological atmosphere for training cadets and preventing destructive and delinquent behavior among students of military institutions.Key words: negative emotional states, subjective well-being, cadets of higher military educational institutions, aggression, depression, anxiety.